Governance, CO 2 emissions and Inclusive Human Development in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study investigates the relevance of government quality in moderating the incidence of environmental degradation on inclusive human development in 44 sub-Saharan African countries for the period 2000-2012. Environmental degradation is measured with CO2 emissions and the governance dynamics include: political stability, voice and accountability, government effectiveness, regulation quality, the rule of law and corruption-control. The empirical evidence is based on the Generalised Method of Moments. Regulation quality modulates CO2 emissions to exert a net negative effect on inclusive development. Institutional governance (consisting of corruption-control and the rule of law) modulates CO2 emissions to also exert a net negative effect on inclusive human development. Fortunately, the corresponding interactive effects are positive, which indicates that good governance needs to be enhanced to achieve positive net effects. A policy threshold of institutional governance a t which institutional governance completely dampens the unfavourable effect of CO2 emissions on inclusive human development is established. Other policy implications are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Economic development; Africa